Interdependence between osteoprotegerin and active von Willebrand factor in long-term cardiovascular mortality prediction in patients undergoing percutaneous coronary intervention - Siller-Matula, Jolanta M.; Lang, Irene M.; Schoergenhofer, Christian; Roest, Mark; Jilma, Bernd (Thrombosis and Haemostasis, 2017)
The interdependence of the predictive accuracy of serum osteoprotegerin (OPG) and von Willebrand factor (vWF) levels for long-term cardiovascular outcomes has not been investigated so far. This was a prospective observational cohort study in 361 patients with coronary artery disease undergoing percutaneous coronary intervention (PCI). Baseline levels of OPG, vWF, active vWF (act vWF) and ristocetin cofactor activity (vWF:RICO) were measured. Cardiovascular mortality was recorded over a median of five years. OPG concentrations >3.7 µg/ml emerged as the strongest predictor of cardiovascular (CV) death: 30 % of patients died during the five-year follow-up in this group, as compared to 10 % in patients with OPG ≤3.7 µg/ml (p<0.001). Act vWF had a significant prognostic impact on CV mortality when OPG levels were low (≤3.7 µg/ml): patients with act vWF concentration >1 µg/ml died in 14 %, whereas those with act vWF values ≤1 µg/ml had a mortality rate of 1 % (p=0.015). We stratified patients into three groups: high OPG, low OPG/high act vWF and low OPG/low act vWF. Patients with high OPG values had a 13-fold higher risk for CV death than those with low OPG/low act vWF concentrations (adj. HR: 12.6; 95 %CI: 1.7–94.7; p=0.014), and a two-fold higher risk as compared to those patients with low OPG/high act vWF concentrations (adj. HR: 2.0; 95 %CI: 1.1–3.7; p=0.03) in the adjusted Cox regression analysis. In conclusion, elevated OPG at the time of PCI was a strong independent predictor of five-years cardiovascular mortality, whereas act vWF had a significant prognostic impact on CV mortality when OPG levels were low.
Keywords: Osteoprotegerin; active von Willebrand factor; cardiovascular death; coronary artery disease; mortality